2014
DOI: 10.1007/s00784-014-1343-x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in young women having a low calcium and vitamin D nutritional status

Abstract: Although caries progression is a complex process involving multiple factors, an adequate nutritional status of Ca and vitamin D could be an additional factor that may help preserve a good oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
15
1
1
Order By: Relevance
“…Moreover, the CaI/protein intake index correlated negatively with tooth loss. No correlations were found between 25(OH)D levels and the studied parameters, which contrasts with the previously cited reports on the impact of vitamin D deficiency on the susceptibility to carries (Antonenko et al 2015).…”
Section: Tooth Carriescontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, the CaI/protein intake index correlated negatively with tooth loss. No correlations were found between 25(OH)D levels and the studied parameters, which contrasts with the previously cited reports on the impact of vitamin D deficiency on the susceptibility to carries (Antonenko et al 2015).…”
Section: Tooth Carriescontrasting
confidence: 99%
“…Supplementary ultraviolet radiation, vitamin D 3 and vitamin D 2 were associated with a significant reduction in caries compared with no supplement (Hujoel 2013). However, in Antonenko et al (2015) study, who evaluated the association between oral health, calcium intake (CaI) and vitamin D nutritional status in 106 young females, there was a negative correlation between CaI and caries, as measured by the decayed-missing-filled teeth index and Löe Silness plaque index. Moreover, the CaI/protein intake index correlated negatively with tooth loss.…”
Section: Tooth Carriesmentioning
confidence: 96%
“…[35][36][37] Interestingly, patients diagnosed with vitamin D deficiency and low calcium values have more dental enamel defects and caries when compared with healthy children. 34,38,39 The relation between a low calcium content in saliva and caries has also been reported. 36,37 It is suggested that lower values greater prevalence of decayed teeth (5.7 ± 1.0 vs. 1.5 ± 0.5, p = 0.001) and lower prevalence of filled teeth than the control group (0.7 ± 0.4 vs. 2.7 ± 0.8, p = 0.037), as shown in Figure 1.…”
Section: ■ Discussionmentioning
confidence: 97%
“…The disease is known to progress with increasing age, and the primary cause is thought to be derived by an imbalance between bone-forming osteoblasts and bone-resorbing osteoclasts due primarily from postmenopausal estrogen deficiencies [1][2][3][4][5]. Over 200 million people are now estimated to be suffering from the disease worldwide with the great majority being white or Asian women over the age of 65 [6].…”
Section: Introductionmentioning
confidence: 99%